Strategi Think-Talk-Write dalam Pembelajaran Menulis untuk Mengembangkan Kreativitas Siswa Sekolah Menengah Pertama - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to assess the effectiveness of the Think-Talk-Write (TTW) strategy in teaching writing to develop the creativity of junior high school students. The method used was a literature review, analyzing various scientific sources, including national and international journals, books, and research reports relevant to the topic of TTW and writing. The results of the study indicate that the Think-Talk-Write strategy significantly contributes to improving students' writing skills, particularly in the areas of idea development, writing organization, and creative expression. The "think" stage helps students process ideas independently, the "talk" stage allows for social interaction to enrich perspectives, and the "write" stage provides a means for actualizing ideas in a more structured written form. Furthermore, the implementation of TTW has been shown to increase students' confidence in writing and encourage active involvement in the learning process. Student creativity develops through freedom of expression, collaborative discussions, and broader exploration of ideas. However, the effectiveness of this strategy is influenced by the teacher's readiness to manage the learning process and the availability of adequate time. Therefore, the Think-Talk-Write strategy can be an innovative alternative in teaching writing in junior high schools to optimally develop student creativity.